Peran Kepuasan Kerja dalam Relasi Work-Life Balance dan Turnover Intention - Charwin Charwin; Agustinus Setyawan2 (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aimed to find the influence of with Job Satisfaction (JS) as the mediator of Work Life Balance (WLB) on Turnover Intention (TI) in Batam. Methodology/approach: This research utilized quantitive approach, likert scale for measuring the questionnaire via purposive sampling. Utilizing data gathered from Batam statisctic center, It was known that Batam has 589.402 active manpower in 2024 gathered as the population of this research. By implementing Slovin formula, the researcher concluded with 400 samples whom filled 13 questions using google form regarding the measured variabels which were processed by using Partial Least Square-Structural Equation Modeling (PLS-SEM) method in SmartPLS 3 statistical software program. Results/findings: The results indicate that Work Life Balance has insignificant effect on Turnover Intention, while Job Satiscation has a significant effect on Turnover Intention, and Job Satisfaction as a moderator variable succesfully strengthens the influence of Work Life Balance over Turnover Intention. Conclusions: Based on the result, Work Life Balance does not affect Turnover Intention as people might not perceive it as a problem. However, the former does affect Job Satisfaction which in return affecting Turnover Intention. Job Satisfation might be a core value for balancing the Turnover Intention. Limitations: This research is limited by a few factors such as the limited sample solely from one region and sector generalization. Contribution: In conclusion, this research contributes to the need of enriching a company management based on human values by providing a valuable manpower insights particularly in Batam.